THE EFFECT OF MATCHING GAMES FOR TEACHING SPEAKING SKILLS - Meilina Haris Mayekti; Ade Christanty Yudha Bestari (Faculty of Social, Economics and Humanities, 2022)
Speaking for general communication is compulsory subject that must be taken by students during second semester. In reality, most of the students at Universitas Nahdlatul Ulama Purwokerto face some problems related to speaking skill. To improve the students’ speaking skill, the lecturers need to know what media is the most suitable for the students. This research is purposed to find out whether matching game can be an effective strategy for teaching speaking. The method of research was experimental research especially quasi-experimental research. The techniques of collecting data were pre-test and post-test. There were two classes as the subject of this research. They are experimental group and control group. Experimental group consists of 20 students and control group consists of 18 students. The result of the data analysis showed that matching game is effective for teaching vocabulary. The value of t- test was higher than the t-table. The result of t-test formula was 1.86, and the t- table was 1.68. Overall, matching game can be an effective strategy for teaching speaking. It can help students to learn speaking easily and effectively.